2021
DOI: 10.1111/jmwh.13305
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Doulas of Color on their Role in Alleviating Racial Disparities in Birth Outcomes: A Qualitative Study

Abstract: Introduction The purpose of this study was to explore how doulas of color conceptualize both their work and how their racial and ethnic identities influence their work within the context of racial disparities in birth outcomes in the United States. Methods We conducted semistructured qualitative interviews with doulas of color who had attended at least 3 births as doulas. Participants were recruited from across the United States. The interviews were audio recorded and transcribed verbatim. Qualitative content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…The authors state that the trained doulas are the liaisons to the Black community, who will increase trust, build relationships, and increase open communication between patients and providers for shared decision-making. In a 2021 qualitative study by Kathawa and coauthors, the findings reinforced the hypothesis that doulas of color are uniquely well suited to support women of color and that tensions surrounding race discordance between women and providers can be alleviated by the presence of a doula from a similar background to the birthing person [21]. The perinatal doula training program described in the Standard article recognized the need to enhance traditional birth doula training with content that would create more culturally appropriate and concordant doula training.…”
Section: Sdm and Racially Concordant Carementioning
confidence: 87%
“…The authors state that the trained doulas are the liaisons to the Black community, who will increase trust, build relationships, and increase open communication between patients and providers for shared decision-making. In a 2021 qualitative study by Kathawa and coauthors, the findings reinforced the hypothesis that doulas of color are uniquely well suited to support women of color and that tensions surrounding race discordance between women and providers can be alleviated by the presence of a doula from a similar background to the birthing person [21]. The perinatal doula training program described in the Standard article recognized the need to enhance traditional birth doula training with content that would create more culturally appropriate and concordant doula training.…”
Section: Sdm and Racially Concordant Carementioning
confidence: 87%
“…A critical first step is recognizing doulas as essential and valuable providers and formally integrating them into the maternal care system through equitable reimbursement and payment 26,37 . The experiences and perspectives of both patients and providers of color should inform all doula training and education, which in the US, has generally centered on the experience of white, highly resourced patients 27 . Hospitals and health systems should invest directly in community programs, especially given that many aspiring birth workers of color have limited access to training and educational opportunities 27 .…”
Section: Discussionmentioning
confidence: 99%
“…In a study exploring doulas' views on pandemic‐induced changes, concordant doulas had an increased awareness of the unique impacts limited COVID‐19 testing access, disrespect, excessive medical intervention, and restrictions on support people in the labor room had on Black, Indigenous, and People of Color communities 26 . Another study assessing perspectives of doulas of color found that participants felt doulas are able to support clients because they are able to notice instances of poor treatment and negative hospital encounters due to personal experience and are more likely to validate such challenges rather than dismiss them 27 . Moreover, Black doulas emphasized the role of intuition in the perinatal care experience, referencing the historical origins of Black midwifery 27 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States, doula support is often a commercial enterprise, and doulas and their clients are predominantly white middle-class women (Hunter 2012, 318). Although there are grassroots doula organizations, such as black doulas helping black mothers achieve a positive birth experience in racist hospital environments (Lakhani 2019), the dominant US doula practice focuses on a white, middle-class clientele (Kathawa et al 2021;Lantz et al 2005).…”
Section: The History and Relevance Of Doula Supportmentioning
confidence: 99%